KINERJA LEMBAGA LEGISLATIF KOTA BONTANG, KALIMANTAN TIMUR TAHUN 2014 – 2019 - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
This research iswilling to know about the legislative organization in Bontang/ This city is in East Kalimantan which is rich of energy like gas, oil and coal.  This city is a municipal one and leaded by a woman mayer, she is dr. Neny.  The legislative organization crasists of fraction, board of budget and Board of honour.  Each strucyut has a chairman, a secretary, a treasure and member the job of the legislative tasks are to superosi…., to make budget and to make regional regulation together with the executive organization.  The term of legislative structure is 5 years.  They are from political partiens